Egg consumption, cholesterol intake, and risk of incident stroke in men: the Kuopio Ischaemic Heart Disease Risk Factor Study. Issue 1 (16th May 2019) - Abdollahi, Anna M; Virtanen, Heli E K; Voutilainen, Sari; Kurl, Sudhir; Tuomainen, Tomi-Pekka; Salonen, Jukka T; Virtanen, Jyrki K
ABSTRACT: Background: Epidemiologic studies suggest inverse associations between consumption of egg, a major source of dietary cholesterol, and stroke. However, the evidence of the relation remains limited, especially among carriers of apolipoprotein E4 (apoE4), which influences cholesterol metabolism. Objective: The aim of this study was to investigate associations of egg and cholesterol intakes with risk of stroke and with the major stroke risk factor, blood pressure, in middle-aged and older men from eastern Finland and whether apoE phenotype could modify these associations. Methods: A total of 1950 men aged 42–60 y in 1984–1989 were included at the baseline examinations of the prospective population-based Kuopio Ischaemic Heart Disease Risk Factor Study. Data on apoE phenotype were available for 1015 men. Dietary intakes were assessed with 4-d food records at baseline and incident stroke events were assessed by record linkage to hospital discharge registries. Cox proportional hazards regression analyses were used to estimate associations with stroke risk. Associations with baseline blood pressure were evaluated with ANCOVA. Results: During the mean ± SD follow-up of 21.2 ± 7.2 y, there were 217 incidences of any stroke: 166 of ischemic stroke and 55 of hemorrhagic stroke. Comparing the highest egg intake quartile with the lowest, the multivariable-adjusted HRs were 0.81 for total stroke (95% CI: 0.54, 1.23; P -trend = 0.32), 0.84 for ischemic stroke (95% CI: 0.53, 1.34; P -trend = 0.44), and 0.75 for hemorrhagic stroke (95% CI: 0.32, 1.77; P -trend = 0.40). The respective HRs for the highest cholesterol intake quartile compared with the lowest were 0.86 (95% CI: 0.57, 1.32; P -trend = 0.42), 0.74 (95% CI: 0.46, 1.20; P -trend = 0.32), and 1.10 (95% CI: 0.45, 2.66; P -trend = 0.75). Diastolic blood pressure was 1.6 mm Hg ( P -trend = 0.04) lower in the highest egg intake quartile compared with the lowest, but there were no associations with systolic blood pressure or with cholesterol intake. ApoE phenotype (32% had apoE4 phenotype) did not modify the associations. Conclusion: Neither egg nor cholesterol intakes were associated with stroke risk in this cohort, regardless of apoE phenotype. This trial was registered at www.clinicaltrials.gov as NCT03221127.